POSSIBLE WAYS OF USING ASH AND SLAG WASTE - P.S. Dmitriyev; T.N. Lyssakova; M. M. Tayzhanova (Academic Journal of Physical and Chemical Sciences, 2019)
A lot of TPPs operate on coal, as there are large coal reserves in the world. Particularly cheap are multi-ash coals. As a result, in addition to the impact of energy enterprises on the atmosphere, there arises the problem of the need to store the ash and slag formed, as a result, huge ash dumps appear. Ash and slag dumps occupying vast territories alienate them from economic use. The lack of land leads to an increase in the height of ash dumps, which accelerates the ingress of ash into the air basin due to wind erosion. As a result, ash dumps become a source of complex environmental pollution, endanger public health, pose a threat to the animal and plant world. Particularly dangerous are ash dumps located near water bodies, since the risk of the rapid spread of ash and slag with water flows in case of emergency increases sharply.